POLA LUKA PADA GENITALIA WANITA KORBAN PERKOSAAN DI RS. BHAYANGKARA TK II MEDAN DARI TAHUN 2018 - 2019 - KHOFIFAH INDRAWATI TANJUNG; ABDUL GAFAR (JURNAL ILMIAH MAKSITEK, 2021)
Cases of sexual violence, namely rape, are still happening. We can see this with information from various print media,electronic media and mass media. Rape cases often cause deep trauma or scars on the victim's body which can be used asevidence. To determine the pattern of genital wounds of women victims of rape in hospital. Bhayangkara TK.II Medan from2018-2019. This study used a descriptive method with a retrospective approach based on the results of secondary data frompost mortem et repertum in cases of rape at the Hospital of Bhayangkara TK.II Medan which were taken by total sampling. Itwas found that the victims with the most data were aged 12-16 years, as many as 96 victims (46.2%) who had torn woundsand were located in Hymen as many as 201 victims (91.4%), with the direction of hymen tears at 6 o'clock as many as 152victims (11.6%). Teenagers with tearing wounds in the hymen position at 6 o'clock are most victims of rape.